Symbiotic Nodule Development and Efficiency in the Medicago truncatula Mtefd-1 Mutant Is Highly Dependent on Sinorhizobium Strains. (24th September 2022) - Jardinaud, Marie-Françoise; Carrere, Sebastien; Gourion, Benjamin; Gamas, Pascal
Abstract: Symbiotic nitrogen fixation (SNF) can play a key role in agroecosystems to reduce the negative impact of nitrogen fertilizers. Its efficiency is strongly affected by the combination of bacterial and plant genotypes, but the mechanisms responsible for the differences in the efficiency of rhizobium strains are not well documented. In Medicago truncatula, SNF has been mostly studied using model systems, such as M. truncatula A17 in interaction with Sinorhizobium meliloti Sm2011. Here we analyzed both the wild-type (wt) A17 and the Mtefd-1 mutant in interaction with five S. meliloti and two Sinorhizobium medicae strains. ETHYLENE RESPONSE FACTOR REQUIRED FOR NODULE DIFFERENTIATION ( MtEFD ) encodes a transcription factor, which contributes to the control of nodule number and differentiation in M. truncatula. We found that, in contrast to Sm2011, four strains induce functional (Fix+) nodules in Mtefd-1, although less efficient for SNF than in wt A17. In contrast, the Mtefd-1 hypernodulation phenotype is not strain-dependent. We compared the plant nodule transcriptomes in response to SmBL225C, a highly efficient strain with A17, versus Sm2011, in wt and Mtefd-1 backgrounds. This revealed faster nodule development with SmBL225C and early nodule senescence with Sm2011. These RNA sequencing analyses allowed us to identify candidate plant factors that could drive the differential nodule phenotype. In conclusion, this work shows the value of having a set of rhizobium strains to fully evaluate the biological importance of a plant symbiotic gene.